Effect of Body Mass Index (BMI) on Prognosis, Response to Therapy, and Surgical Outcomes in Various Subtypes of Breast Cancer: A Systematic Review - Himawan Ridho; Arfiyanti; Arif Rachman (Bajang Institute, 2026)
Breast cancer management is increasingly complicated by the global obesity crisis. While elevated Body Mass Index (BMI) worsens prognosis, its exact effect on treatment response and survival across subtypes remains unclear. This systematic review evaluates how BMI impacts prognosis, pharmacological efficacy, and oncoplastic surgical outcomes to support personalized Evidence-Based Medicine (EBM). Following PRISMA guidelines, we conducted a qualitative narrative synthesis using the PICO framework to search databases up to 2026. We included observational studies and retrospective RCT analyses that correlated baseline BMI in adult women with overall survival, pathological complete response, and surgical complications. Because BMI cut-offs varied across studies, we assessed methodological quality using the Newcastle-Ottawa Scale (NOS) and applied a descriptive analytical approach to synthesize the findings.